2016
DOI: 10.1080/09658211.2016.1222443
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Ranschburg effects: facilitation and inhibitory repetition effects analogous to verbal memory

Abstract: The present paper examines the effect of within-sequence item repetitions in tactile order memory. Employing an immediate serial recall (ISR) procedure, participants reconstructed a 6-item sequence tapped upon their fingers by moving those fingers in the order of original stimulation. In Experiment 1a, within-sequence repetition of an item separated by 2-intervening items resulted in a significant reduction in recall accuracy for that repeated item (i.e. the Ranschburg effect). In Experiment 1b, within-sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
(90 reference statements)
4
7
0
Order By: Relevance
“…Inhibition functions to prevent perseveration of items with high activation levels, and this is a crucial feature for ordinal models of memory that utilise a primacy gradient (e.g., Page & Norris, 1998). The presence of the Ranschburg effect for visual-verbal stimuli under CA, coupled with preliminary findings of the effect with tactile stimuli (Roe et al, 2016), suggests that these models may be generalisable beyond verbal stimuli presented in conditions of quiet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition functions to prevent perseveration of items with high activation levels, and this is a crucial feature for ordinal models of memory that utilise a primacy gradient (e.g., Page & Norris, 1998). The presence of the Ranschburg effect for visual-verbal stimuli under CA, coupled with preliminary findings of the effect with tactile stimuli (Roe et al, 2016), suggests that these models may be generalisable beyond verbal stimuli presented in conditions of quiet.…”
Section: Discussionmentioning
confidence: 99%
“…At test, they retrieved the sequence by moving their fingers in the order of original presentation. While Roe et al (2016) reported evidence for response inhibition (i.e., the Ranschburg effect), it is possible that participants verbally recoded the tactile stimulations, thereby exhibiting the previously observed verbal Ranschburg effect (e.g., Crowder, 1968;Duncan & Lewandowsky, 2005;Henson, 1998a;Jahnke, 1969).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Roe et al (2017) argued that their finding reflected processes within non-verbal memory and was, therefore, evidence in support of a cross-modal Ranschburg effect. However, one caveat to their argument is the possibility that their pattern of data merely reflected a process in which the tactile sequences were recoded into verbal representations (as originally supposed by Mahrer & Miles, 2002).…”
Section: Introductionmentioning
confidence: 89%
“…Notwithstanding the use of CA, and the resilience of the Ranschburg effect in Johnson et al (2018), their to-be-remembered sequences comprised verbal stimuli. In an attempt to minimise further the probability for verbal recoding of the to-be-remembered sequences, Roe, Miles, and Johnson (2017) tested ISR for tactile sequences. Here, for the presentation phase, visually obfuscated participants received sequences of six-individual stimulations to each of six fingers.…”
Section: Introductionmentioning
confidence: 99%